Estudio de factibilidad para la creación del centro de atención al ciudadano (CAC) del Gobierno Autónomo Descentralizado Municipal del cantón San Jacinto de Buena Fé, año 2013 - Verduga León, Yaco Boris (2013)
The object of study is working determined as far as the Citizen Self-Government of the Canton Decentralized good faith, under the administration of his solicitor, Don Luis Zambrano Bello in the period from 2009 to 2014. This research was conducted in the Canton Buena Fé province of Los Ríos, Ecuador. We highlight the work of the current municipal administration that is being developed for the benefit of citizen’s buenafesinos, in urban and rural parishes. Due to the importance of the municipal government and its rapid population growth, it is essential to suggest the Mayor of Canton and his councilors, to prioritize the implementation of the Citizen Service Center, as an important component of the management performs the council. Our intention is to focus the importance of demand draft CAC contributing specifically to the development of public and private activities, creating an environment of modernization in the provision of goods and services. It is very important to take into account the support of the people, since they are directly involved in the care changes that GAD can provide. With a stakeholder analysis, citizens are the core of the project, which is involved in providing services in an agile, modern and comfortable, and this is the most important indicator in the creation of public policies. The scope includes the feasibility study for the creation of the Center for Citizen CAC, looking for maximum benefit at minimum cost and generation by providing resources for better implementation of public goods and services and private.